Increased hippocampal tail volume predicts depression status and remission to anti-depressant medications in major depression. Issue 8 (August 2018) - Maller, J; Broadhouse, K; Rush, A; Gordon, E; Koslow, S; Grieve, S
Abstract Studies of patients with major depressive disorder (MDD) have consistently reported reduced hippocampal volumes; however, the exact pattern of these volume changes in specific anatomical subfields and their functional significance is unclear. We sought to clarify the relationship between hippocampal tail volumes and (i) a diagnosis of MDD, and (ii) clinical remission to anti-depressant medications (ADMs). Outpatients with nonpsychotic MDD (n =202) based on DSM-IV criteria and a 17-item Hamilton Rating Scale for Depression (HRSD17 ) score ⩾16 underwent pretreatment magnetic resonance imaging as part of the international Study to Predict Optimized Treatment for Depression (iSPOT-D). Gender-matched healthy controls (n =68) also underwent MRI scanning. An automated pipeline was used to objectively measure hippocampal subfield and whole brain volumes. Remission was defined as an HRSD17 of ⩽7 following 8 weeks of randomized open-label treatment ADMs: escitalopram, sertraline or venlafaxine-extended release. After controlling for age and total brain volume, hippocampal tail volume was larger in the MDD cohort compared to control subjects. Larger hippocampal tail volume was positively related to clinical remission, independent of total hippocampal volume, total brain volume and age. These data provide convergent evidence of the importance of the hippocampus in the development or treatment of MDD. Hippocampal tail volume is proposed as a potentially useful biomarker of sensitivity to ADM treatment.